Reduction of Symplectic Lie Algebroids by a Lie Subalgebroid and a Symmetry Lie Group - Iglesias, D.; Marrero, J.C.; Martín de Diego, D.; Martínez, E.; Padrón, E. (Symmetry, Integrability and Geometry: Methods and Applications, 2007)
We describe the reduction procedure for a symplectic Lie algebroid by a Lie subalgebroid and a symmetry Lie group. Moreover, given an invariant Hamiltonian function we obtain the corresponding reduced Hamiltonian dynamics. Several examples illustrate the generality of the theory.